2022
DOI: 10.2320/matertrans.mt-m2021162
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Dynamic Grain Growth Mechanism Enabling the Control of Microstructure and Texture by High Temperature Deformation: Experimental Evidence and Applicability

Abstract: The relationship between the mechanism of high temperature deformation and the evolution behavior of microstructure and the texture during deformation, which has been found in various solid solution alloys, is clarified. It is shown that the preferential dynamic grain growth (PDGG) mechanism proposed by the authors can explain the behavior of microstructure change as well as texture change of all studied alloys without contradiction. The essential aspect of the PDGG mechanism is the preferential growth of crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Fukutomi et al suggested that the texture orientation in the Al–Mg alloy formed after deformation is associated with a low Taylor factor [ 9 ]. The Taylor factor is determined by the number of slip systems contributing to the deformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fukutomi et al suggested that the texture orientation in the Al–Mg alloy formed after deformation is associated with a low Taylor factor [ 9 ]. The Taylor factor is determined by the number of slip systems contributing to the deformation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this value corresponds to the six perfect-pyramidal II slip systems. Because the cross-slip systems, owing to the SFE, provide dislocation paths, their activation seems to contribute to the increase in the Taylor factor [ 9 ]. This implies that a non-basal texture component can develop in AZ31, the component most similar to that of the pure state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig.14 に,850℃にて一次再結晶焼鈍した後に常温引張試験した試料の結晶方位マップおよび KAM マップを示す。{111}<112>方位粒は{411}<148>方位粒よりも KAM 値が高い ことが確認された。一般的に,加工により蓄積される歪量は結晶方位により異なり21- 23,25,26,28) ,Taylor 因子が関係することが知れているが[21][22][23]25,26) ,今回の結果は,引張変形に 対して{111}<112>方位粒は{411}<148>方位粒よりも歪が蓄積しやすい結晶方位であること を示唆するものと推察される。一方,いずれの方位粒においても,結晶粒径が小さいほど KAM 値が高い傾向が認められた。さらに,粒内の KAM 値分布も均一ではなく,粒界近 傍にて KAM 値が高い傾向が確認された。これは,6%程度の変形量においては,粒内より も粒界近傍の不均一変形領域で転位が堆積しやすい傾向が顕著であるためと推定される。 前項までの考察に使用した Average Misorientation は,各粒における KAM 値の平均値であ り,小さな結晶粒ほど粒界近傍領域の占める割合が大きいため,粒界の影響を受けやすい と考えられる。{111}<112>方位粒は,相対的に粒径が小さいことも影響して他の方位粒よ り歪が蓄積されやすく,850℃の高温においても同様の現象が生じたと推察される。な お,850℃での張力焼鈍後の伸び調査において,張力焼鈍前に 850℃にて焼鈍する条件に おいて伸びが小さい傾向が確認された。Fig. 14 は常温引張試験の結果であるが,高温引張…”
unclassified